Effects of pH and Temperature on Water under Pressurized Conditions in the Extraction of Nutraceuticals from Chaga (Inonotus obliquus) Mushroom - Ibrahim M. Abu-Reidah; Amber L. Critch; Charles F. Manful; Amanda Rajakaruna; Natalia P. Vidal; Thu H. Pham; Mumtaz Cheema; Raymond Thomas (MDPI AG, 2021)
Currently, there is increased interest in finding appropriate food-grade green extraction systems capable of extracting these bioactive compounds from dietary mushrooms for applications in various food, pharmacological, or nutraceutical formulations. Herein, we evaluated a modified Swiss water process (SWP) method using alkaline and acidic pH at low and high temperature under pressurized conditions as a suitable green food grade solvent to obtained extracts enriched with myco-nutrients (dietary phenolics, total antioxidants (TAA), vitamins, and minerals) from Chaga. Ultra-high performance liquid chromatography coupled to high resolution accurate mass tandem mass spectrometry (UHPLC-HRAMS-MS/MS) was used to assess the phenolic compounds and vitamin levels in the extracts, while inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the mineral contents. Over 20 phenolic compounds were quantitatively evaluated in the extracts and the highest total phenolic content (TPC) and total antioxidant activity (TAA) was observed at pH 11.5 at 100 °C. The most abundant phenolic compounds present in Chaga extracts included phenolic acids such as protocatechuic acid 4-glucoside (0.7-1.08 µg/mL), syringic acid (0.62-1.18 µg/mL), and myricetin (0.68-1.3 µg/mL). Vitamins are being reported for the first time in Chaga. Not only, a strong correlation was found for TPC with TAA (r-0.8, <0.0001), but also, with individual phenolics (i.e., Salicylic acid), lipophilic antioxidant activity (LAA), and total antioxidant minerals (TAM). pH 2.5 at 100 °C treatment shows superior effects in extracting the B vitamins whereas pH 2.5 at 60 and 100 °C treatments were outstanding for extraction of total fat-soluble vitamins. Vitamin E content was the highest for the fat-soluble vitamins in the Chaga extract under acidic pH (2.5) and high temp. (100 °C) and ranges between 50 to 175 µg/100 g Chaga. Antioxidant minerals ranged from 85.94 µg/g (pH7 at 100 °C) to 113.86 µg/g DW (pH2.5 at 100 °C). High temperature 100 °C and a pH of 2.5 or 9.5. The treatment of pH 11.5 at 100 °C was the most useful for recovering phenolics and antioxidants from Chaga including several phenolic compounds reported for the first time in Chaga. SWP is being proposed herein for the first time as a novel, green food-grade solvent system for the extraction of myco-nutrients from Chaga and have potential applications as a suitable approach to extract nutrients from other matrices. Chaga extracts enriched with bioactive myconutrients and antioxidants may be suitable for further use or applications in the food and nutraceutical industries.